Severe pneumonitis refractory to steroids following anti-PD-1 immunotherapy. (8th October 2018) - Andruska, Neal; Mahapatra, Lily; Hebbard, Carleigh; Patel, Priyank; Paul, Vishesh
Abstract : Anti-programmed death 1 (PD-1) immune checkpoint inhibitors enhance the antitumour activity of the immune system and have produced durable tumour responses in several solid tumours including non-small cell lung cancer (NSCLC). However, PD-1 inhibitors can lead to immune-related adverse events, including pneumonitis, which is typically mild, but can be severe and potentially fatal. Pneumonitis often resolves with steroids, but some cases are steroid refractory, leading to a relapsing and remitting course in milder cases or the need for salvage therapies in more severe cases. Here, we present two patients with NSCLC who developed severe pneumonitis following therapy with nivolumab and pembrolizumab. While one patient improved with steroids and infliximab, the other patient failed to respond to steroids and subsequently died. These cases demonstrate the highly variable presentation and therapeutic responses seen in patients with pneumonitis following anti-PD-1 therapy and illustrate that severe cases can often present refractory to steroid therapy.